IMPLEMENTASI BLENDED LEARNING PADA MATA PELAJARAN MATEMATIKA SISWA SD ISLAM BANI HASYIM SINGOSARI MALANG - Dewi Zakiyah; Anwar Sa’dullah; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The purpose of this research is to describe the implementation, evaluation and obstacles base on experience in blended learning in mathematics subjects of students of SD Islam Bani Hasyim Singosari Malang. In the implementation of mathematics learning, especially during online learning, there are many students who experience difficulties and confusion in doing and understanding the mathematical material described by the teacher. The position of the researcher as a full observer and as the main instrument in collecting the data research in the location and as a participant observer. This research use a qualitative approach with descriptive data and case study research. The techniques that used to collected the data through location observations, semi-structured interviews to find out what obstacles are experienced by teachers and students, and documentation of activities related to the implementation of blended learning. Based on the results of the research, the related to the implementation of blended learning includes planning, and the implementation process. The evaluation of the implementation of blended learning in mathematics subjects, and the obstacles experienced and effort (support) that can be made to handle it.